Analysis of the Reformulation of the Minimum Marriage Age: An Islamic Law Perspective on Law No. 16 of 2019 in the Pamekasan Court - Moh Sholihin; Jamiliya Susantin (Binamulia Hukum, 2026)
This study aims to analyze the reformulation of the minimum marriage age under Law No. 16 of 2019 through a comparative perspective of Islamic law and positive law, as well as to examine its implications for judicial practice at the Pamekasan Religious Court. This research employs a socio-legal approach, incorporating statutory, conceptual, and case approaches. Data were collected through documentation of marriage dispensation cases from 2019 to 2025 and interviews with judges. The findings indicate that the reformulation of the minimum marriage age to 19 years for both men and women constitutes a progressive measure to strengthen child protection and promote gender equality. However, the amendment has been followed by a significant increase in applications for marriage dispensation, reflecting a gap between legal norms and prevailing social realities. The study also reveals differences between Islamic law, which is grounded in the concepts of baligh, rusyd, and maslahah, and positive law, which establishes a fixed statutory minimum age for marriage. In judicial practice, judges tend to integrate sociological, psychological, and maslahah considerations when deciding marriage dispensation cases. These findings suggest that the impact of the reform on child protection and the prevention of child marriage remains mixed, highlighting the need for a more comprehensive strategy that combines legal reform with broader social interventions.